Christian-Muslim relations: a bibliographical history / Volume 20 Iran, Afghanistan and the Caucasus (1800-1914) / edited by David Thomas, John Chesworth ; with Reza Pourjavady and Douglas Pratt - Thomas, David; Chesworth, John; Pūrǧawādī, Riḍā; Pratt, Douglas (Christian-Muslim relations a bibliographical history, 2023)
Christian-Muslim Relations, a Bibliographical History 20 (CMR 20)', covering Iran, Afghanistan, Armenia, Azerbaijan and Georgia in the period 1800-1914, is a further volume in a general history of relations between the two faiths from the 7th century to the early 20th century. It comprises a series of introductory essays and the main body of detailed entries. These treat all the works, surviving or lost, that have been recorded. They provide biographical details of the authors, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between numerous new and leading scholars, CMR 20, along with the other volumes in this series, is intended as a fundamental tool for research in Christian-Muslim relations.0